Permanent LDR implants in treatment of prostate cancer - Skowronek, Janusz; Kanikowski, Marek; Zwierzchowski, Grzegorz; Chicheł, Adam (Contemporary Oncology/Współczesna Onkologia, 2009)
Low-dose rate brachytherapy (LDR-BT) is a radiation method known for several years in the treatment of localized prostate cancer. The main idea of this method is to implant small radioactive seeds directly into the prostate gland. LDR brachytherapy is applied as a mo-notherapy and also used along with external beam radiation therapy (EBRT) as a boost. In most cases it is used as a sole radical treatment modality, but not as a palliative treatment. The appli-cation of permanent seed implants is a curative treatment alternative in patients with organ-confined cancer, without extracapsular extension of the tumour. This technique is particularly popular in the United States. In Europe, however, high-dose rate brachytherapy (HDR-BT) is more popular in early-stage prostate cancer treatment (as a boost). The aim of this publication is to describe methods, indications, complications and selected results of prostate cancer LDR brachytherapy.